Heat distribution analysis of cartridge heater in core and cavity of compression mold for bio-composite roof tile fabrication - Al Masta, Muslimin; Rahman, Maulidya; Luqyana, Dhiya; Muhamad, Azam Milah (Jurnal Polimesin, 2024)
Bio-composite roof tiles use polypropylene matrix material and rice straw fiber as reinforcement processed by compression molding to create innovative and sustainable building products. This research aims to analyze heat distribution from the cartridge heater in the mold core during the compression molding process for fabricating bio-composite roof tiles. The research employs Finite Element Analysis (FEA), and laboratory experiments to measure temperature distribution and heating efficiency. The results showed that even heat distribution on the mold core is crucial to ensure optimal final product quality. Manual calculation estimated a heating time of 170.78 seconds to reach the desired temperature. Simulations conducted using Ansys R19.2 software shows that the temperature variation on the surface of the mold core can be minimized with the optimal placement of the heater cartridge. The simulation results obtained a time of 10 seconds to reach a temperature of 200℃ gradually. Laboratory experiments support the simulation results by showing that good heat distribution improves bio-composite tile materials' mechanical strength and homogeneity. This research significantly contributes to the design and optimization of mold cores for bio-composite applications. It offers practical guidance to the industry in improving the efficiency of the production process.